(untitled) - International rice research institute (Laguna, Philippines, 1994)
The book presents different aspects of pest ecology and biology; new data on how mineral nutrition effects disease developments; advances in modeling the effects of several pest populations on rice yield. Finally, the book deals with pest management
Keywords: Field crops,Pesticides,Pests,Plants, protection of,Rice; Diseases and pests,Control,Diseases and pests